Coping with stillbirth: Insights from parents in rural Limpopo, South Africa - Lunghile Shivambo; Dumile Gumede (Journal of Public Health in Africa, 2025)
Background: Stillbirth continues to be a significant global public health issue. Effective coping mechanisms are essential for parents to process their grief and heal after a stillbirth. However, research on how South African parents, particularly in rural areas, cope with stillbirth is limited.